Peut-on encore parler de mission éducative de l’école? - Legault, Georges A.; Jutras, France; Desaulniers, Marie-Paule (Éducation et francophonie, 2002)
This article aims at understanding the social mission of the school in Québec with an analysis of educational purposives at the moment of a major reform in the school curriculum, accompanied by a reform in teacher training. The reform not only leads to the specifications of educational purposives oriented towards social integration, but to an epistemological paradigm as well. Learning no longer means acquiring objectives whose degree of mastery is observable by appropriate behaviours; learning now means developing abilities, which assumes that resources will be mobilized in the doing. The analysis of the stakes of the action rationality allows us to distinguish technical rationality and teleological rationality. Learning by objective refers to the technical rationality which aims at finding effective ways to produce a specific result, while the development of abilities is closer to teleological rationality, an ideal towards which one leans without reaching it once and for all. Formulating educational purposives is actually formulating an ideal of the human being and an ideal of social life. Thus, we try to see to what degree the development of a person’s abilities as an educational purposive in the school institution fits into social purposives.